An Account of Iranian Intermediate EFL Learners' Vocabulary Retention and Recall Through Spaced and Massed Distribution Instructions. Issue 2 (April 2023) - Namaziandost, Ehsan; Razmi, Mohammad Hasan; Atabekova, Anastasia; Shoustikova, Tatyana; Kussanova, Bibigul H.
There has been an ongoing debate on the effectiveness of spaced and massed distribution instruction in second/foreign language learning. A number of studies in the literature have investigated the impacts of spacing effect on English as a Foreign Language (EFL) learners' vocabulary acquisition. This study aims to expand the body of existing research by exploring the impact of spaced versus massed distribution instruction on EFL learners' vocabulary recall and retention. To this end, the Oxford Quick Placement Test (OQPT) was administered to 120 Iranian EFL students to determine their level of English proficiency. Accordingly, 75 intermediate students were selected and randomly assigned to three equivalent groups: two experimental groups, namely spaced instruction ( n = 25) and massed instruction ( n = 25), and one control group ( n = 25). After administering a pretest, the participants in both experimental groups received two different modes of instruction. The massed instruction group attended one intensive session to learn each set of target vocabularies; the spaced instruction group, on the contrary, had three sessions at irregular time intervals to learn the same vocabularies. The control group studied the same vocabularies but received no vocabulary-focused instructions. Overall, 180 vocabularies were taught to the students during a 12-week period (15 vocabularies per week). The instructions in each group took 60 min each week. Using a pretest, posttest, and delayed posttest design, the students first took a receptive vocabulary pretest before the treatment. One week after the treatment, a receptive vocabulary posttest was administered. Finally, after a 4-week interval, the students took the delayed posttest. The results revealed that the spaced instruction group significantly outperformed the massed instruction group on both immediate and delayed posttests. The findings lend support to the modulation of spaced instruction into the curricula in instructional settings as a valuable vocabulary instruction technique to promote vocabulary learning in real classroom environments.